The kinematical analysis of the taekwondo sparring players' Bandal Chagi in kinematics - Ha, C.-S.; Choi, M.-H.; Kim, B.-G. (International Journal of Applied Sports Sciences, 2009)
The purpose of this study is to provide scientific data about the most effective performance of the Bandal Chagi, which is used very frequently in Taekwondo competitions. For this study, to analyze the changes in kinematics, two groups of subjects were selected from welterweight Taekwondo players. One group has four skilled players who have had more than 10-years' experience and got a prize in national championships, while the other group has four unskilled players who have had no experience winning a prize for Taekwondo. For motion analysis, 7 Cameras (MX13) Vicon Motion System captured the kinematic data. Polygon Viewer was used to output the three dimensional data. The results of analyzing the necessary time of action, angle-change in every joint, and changes in body center of mass (com) in kinematics are as follows: 1. when players are in competition, Bandal Chagi can be practiced more effectively if one's knee joint angle-change is larger than the change of the angle between players' supporting leg and kicking leg. 2. Bandal Chagi can be practiced effectively when hip joint`s angle-change forms the maximum flexion at the point where the kicking leg and supporting leg crossover. 3. Bandal Chagi can be performed effectively when one hyper-extends their hip while extending their upper-body. In conclusion, when training for Taekwondo kyorugi competitions, for players to apply the Bandal Chagi more effectively, players must be trained to enhance knee joint, hip joint and extension in pulling back upper-body action.